Leveraging COBIT 2019 to Implement IT Governance in SME Context: A Case Study of Higher Education in Campus A - Diana Utomo; Mahaning Wijaya; Suzanna Suzanna; Efendi Efendi; Noviyanti Tri Maretta Sagala (Bina Nusantara University, 2022)
Achieving business and Information Technology (IT) alignment has become the aspiration of most organizations nowadays. Small and Medium Enterprises (SMEs) are not exempt as they also thrive to survive in a competitive market using IT. However, implementing all IT control and management components will be excessive, with a lack of justifiable cost-benefit for SMEs. A tailored governance system based on the specificities of SMEs is necessitated to help the organization to focus on its main objectives and strategies. By leveraging COBIT 2019 design toolkit, the researchers support Campus A in establishing healthy governance and IT management. Both qualitative and quantitative approaches are applied to select relevant governance/ management objectives. The toolkit has been designed with a semi-automated quantitative approach in which users will get scoring for each objective based on the associated value inputted for each design factor. Through a series of discussions with the management team, it concludes the governance design and recommends several improvements to increase its capability level, from the current level of 1.05 (initial stage) to the desired level of 2.33 (repeatable stage). Then, since the toolkit is practical to use, it is also rigid by design with its predefined and protected formula. To some extent, the resulting score or importance level of certain governance/management objectives is questionable and lacks justification. Flags or indicators to ‘should-have’ governance/management objectives, regardless of the organization’s size and type, will be useful to prevent the omission of essential objectives.